Membangun Sekolah Aman dengan Gerakan Anti Bullying di SDN 1 Astanajapura - Rodiatul Ismayanah; Rizkiyah Rizkiyah; Mirna Safitri; Bagus Nurul Iman; Dadang Kurnia (Journal on Education, 2025)
This study aims to analyze the implementation of the anti-bullying movement in creating a safe school environment at SDN 1 Astanajapura. A descriptive qualitative approach was employed, with data collection techniques including observation, in-depth interviews, and documentation. The primary informants consisted of teachers, students, and parents. The findings revealed that anti-bullying programs, such as social skills training, awareness campaigns on the impacts of bullying, and school-based reporting policies, were effective in raising student awareness and preventing bullying behavior. Furthermore, the role of teachers as facilitators and mentors was crucial in supporting the success of these programs. However, challenges such as low parental involvement and students’ reluctance to report bullying cases still need to be addressed. This study concludes that synergy among schools, students, teachers, and parents is essential to ensure the sustainability of the anti- bullying movement and to create a conducive school environment.